Sex and weight category differences in time-motion analysis of elite judo athletes: Implications for assessment and training - Sterkowicz-Przybycien, K.; Miarka, B.; Fukuda, D. H. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this investigation was to support training program development through the comparison of combat and pause phases during elite male and female judo competition in athletes of varying weight categories. A total of 1,411 video recorded judo matches between athletes who qualified for the 2012 Olympic Games were analyzed. Within the matches, 111,203 competitive situations were categorized as combat (with subphases of approach, gripping, attack, defense, and groundwork) or pause phases. Time-motion analysis data were compared between extra light, light, middle, and heavyweight categories for men and women. Median times varied between sex and weight category groups for individual combat (23.9-28.5 seconds), pause (4.0-8.8 seconds), and combat subphases (p = 0.05). Sex-based differences in accumulated combat and combat subphase times were primarily found in the middleweight athletes. Heavyweight female athletes had longer accumulated groundwork and pause times, extra lightweight women had greater groundwork time, and both extra light and lightweight women had shorter accumulated attack times compared with their male counterparts. No differences between men and women were found for the time to complete an individual combat action; however, the pause phase and most of the combat subphases displayed differences. The lightest and heaviest judo athletes displayed unique characteristics compared with athletes in the other weight categories, particularly in the attack, defense, groundwork, and pause phases. These results have important implications related to training program design and support the need for the development of normative data for male and female judo athletes of varying weight categories.